THE DEFINITION AND ESSENCE OF LAND RELATIONS AS AN ECONOMIC CATEGORY - Dauzova, А. М.; Dyrka, S. (Scientific Journal of Pedagogy and Economics, 2018)
The basis for the formation of efficient agricultural production is the improvement of land relations and the formation of land use system, “adequate to market economy”. Society is in urgent need of transition to fundamentally new type of economic growth - intensive growth of resource-saving type, based on the careful use of natural resources, to achieve ecological balance. Special, outstanding value in the life of society has the earth by itself. It is an essential condition of human existence; an indispensable means of satisfying the most varied needs - economic, social, and aesthetic, etc. Nevertheless, use of land usually refers to its operation in the sphere of production. Rational use of land resources is the great importance in the economy of agriculture and the country as a whole. In the sphere of human production, the role of land is quite important. In industry, transport and urban planning it is used as foundation, spatial operational basis for the location of production. Land becomes more important in the extractive industry, where it serves as the source of raw materials. The process of production doesn’t depend on the quality of the soil, topography and many other landproperties.